Clinical characteristics and complications of patients with type 2 diabetes attending an urban hospital in Bangladesh. Issue 1 (January 2015) - Islam, Sheikh Mohammed Shariful; Alam, Dewan S.; Wahiduzzaman, Mohammed; Niessen, Louis W.; Froeschl, Guenter; Ferrari, Uta; Seissler, Jochen; Rouf, H.M.A.; Lechner, Andreas
Abstract Aims To investigate the clinical features of patients with type 2 diabetes on oral medication and determine the complications and risk factors in these patients. Methods A cross-sectional was conducted among 515 patients with type 2 diabetes at the outpatient clinics of Bangladesh Institute of Health Science (BIHS) hospital from September to December 2013. We collected data on socio-economic characteristics, clinical status, risk factors, complications, anthropometric measurements and blood tests. Univariate and multivariate logistic regression was performed to identify risk factors associated with diabetes complications. Results The mean(±SD) age of the participants was 50.0(±10.1) years and 15.3% were less than 40 years. The mean HbA1c was 8.3(±2.1). Only 28.7% of the participants achieved targets for HbA1c. The overall prevalence of hypertension, obesity and dyslipidemia was 57.5%, 62.6% and 72.7%, respectively. Eye problems were the most common complication (68.9%) followed by chronic kidney diseases (21.3%) and cardiovascular diseases (11.8%). There were significant associations between the complications and age, duration of diabetes and duration of hypertension. In the multivariate analysis adjusting for other confounding variables, only systolic blood pressure was found to be significantly associated with complications [OR 0.809, 95% CI 0.666–0.981 (p-value 0.031)]. Conclusion Results of the study confirm that even under best clinical settings a great majority Bangladeshi adults with type 2 diabetes have uncontrolled diabetes and a high prevalence of risk factors that might contribute to early development of complications. Early screening of high risk groups and proper management of diabetes is recommended to avoid early complications.